Echocardiographic predictors of new-onset atrial arrhythmias in patients undergoing hematopoietic stem cell transplantation. (15th September 2021) - Singh, Nikhil; Singh, Amita; Besser, Stephanie A.; Lang, Roberto M.; Mor-Avi, Victor; Kosuri, Satyajit; Bishop, Michael R.; DeCara, Jeanne M.
Abstract: Background: Atrial arrhythmias following hematopoietic stem cell transplantation (HSCT) have been associated with increased length of stay, need for intensive care, and increased mortality within one-year post-transplant. We sought to identify echocardiographic parameters that may predict the development of new atrial arrhythmias post-HSCT. Methods: We performed a retrospective chart review of 753 consecutive patients who underwent HSCT at the University of Chicago from January 2015 through December 2019. Patients with baseline echocardiogram within 6 months prior to transplantation were included. Those with prior transplants, history of atrial arrhythmias, or unavailable echocardiographic images were excluded, resulting in 187 patients included for final analysis. Baseline clinical and demographic variables, as well as echocardiographic parameters, were compared between patients who developed new atrial arrhythmias post-HSCT versus those who did not. Results: Of the 187 patients included for analysis, 25 (13%) developed new atrial arrhythmias, with 13 of these occurring within 30 days of transplantation. Despite no significant difference in left atrial (LA) end-systolic volume between those with and without new arrhythmia following HSCT (OR 1.04; 95% CI 0.91–1.09, p = 0.233), univariable analysis demonstrated that patients who developed atrial arrhythmias had reduced LA function, as reflected by lower LA emptying fraction (OR 0.94; 95% CI 0.91–0.98, p = 0.003) and lower LA reservoir strain (OR 0.95; 95% CI 0.92–0.99, p = 0.009). Conclusions: Echocardiographic indices of LA function, namely LA emptying fraction and LA reservoir strain, can identify patients at risk for developing new atrial arrhythmias post-HSCT, prior to the development of morphologic changes in the LA. Highlights: The development of atrial arrhythmias portends increased risk of mortality post-HSCT. LA reservoir strain predicts risk of arrhythmias prior to morphologic changes of the chamber. In at-risk patients, targeted therapies and close follow-up may be warranted.